Subcutaneous and visceral fat assessment by DXA and MRI in older adults and children. Issue 4 (6th March 2022) - Maskarinec, Gertraud; Shvetsov, Yurii B.; Wong, Michael C.; Garber, Andrea; Monroe, Kristine; Ernst, Thomas M.; Buchthal, Steven D.; Lim, Unhee; Le Marchand, Loïc; Heymsfield, Steven B.; Shepherd, John A.
Abstract: Objective: Given the importance of body fat distribution in chronic disease development, feasible methods to assess body fat are essential. This study compared dual‐energy x‐ray absorptiometry (DXA) in measuring visceral and subcutaneous adipose tissue (VAT and SAT) with magnetic resonance imaging (MRI). Methods: VAT and SAT were assessed using similar DXA and MRI protocols among 1, 795 elderly participants of the Adiposity Phenotype Study (APS) and 309 children/adolescents in Shape Up! Kids (SKids). Spearman correlations, Bland–Altman plots, and coefficients of determination ( R 2 ) assessed agreement between DXA and MRI measures. Results: DXA overestimated SAT values in APS (315 vs. 229 cm 2 ) and SKids (212 vs. 161 cm 2 ), whereas DXA underestimated VAT measures (141 vs. 167 cm 2 ) in adults only. The correlations between DXA and MRI values were stronger for SAT than VAT (APS: r = 0.92 vs. 0.88; SKids: 0.90 vs. 0.74). Bland–Altman plots confirmed better agreement for SAT than VAT despite differences by sex, ethnicity, and weight status with respective R 2 values for SAT and VAT of 0.88 and 0.84 (APS) and 0.81 and 0.69 (SKids). Conclusion: These findings indicate that SAT by DXA reflects MRI measures in children and older adults, whereas agreement for VAT is weaker for individuals with low VAT levels.